Development of Android-Based Multimedia Media (M2BA) to Improve Students' Chronological Thinking in Indonesian History Learning in the Pre-aksara Period - Folanda, Gio; Ofianto, Ofianto (Master Program of Social Science Education of Universitas Negeri Padang, Indonesia, 2022)
This study aims to describe the media design process and produce appropriate, practical, and effective media to improve chronological thinking skills and as a solution to the lack of variety of media used by teachers and students' lack of chronological thinking skills, M2BA products were developed. The results of this study were obtained from the description of the first stage of research, namely needs analysis as a supporting factor for the need for M2BA media development. At the development stage, a media draft is produced which will be tested for feasibility by experts and the results of the analysis of the feasibility test for material experts obtained an average of 3.46, media experts with an average of 3.4, and linguists with an average of 3.41 from expert judgment. eligible criteria. The effectiveness test with independent sample t-test posttest control class and posttest experimental class then obtained the value of sig. (2-tailed) 0.000 <0.05 in the sense that Ha is accepted and Ho is rejected. In other words, there is an effect of using M2BA on students' chronological thinking skills. This study concludes that M2BA media is feasible, practical and effective use in improving students' chronological thinking skills in learning Indonesian history in the pre-literacy period.